Analysis of the management of heatlh operasional assistance funds on the achievement of minimum service standards in the productive age sei agul community health center, Medan city - Andreansyah, Risky; Gurning, Fitriani Pramita; Susanti, Nofi (Institute of Computer Science (IOCS), 2025)
Health is an important aspect for both individuals and the wider population. WHO (World Health Organization) is the largest health organization in the world which covers world health by distributing health aid funds to policies which will later become a reference for various countries to implement. The aim of this research is to determine the Management of Health Operational Assistance Funds (BOK) towards the Achievement of Minimum Service Standards (SPM) in the Productive Age Service Sector at the Sei Agul Community Health Center, Medan City. This research is qualitative research with an in-depth case study approach. This research involved four informants who understand, know and understand, namely the Head of the Community Health Center, the BOK Treasurer, the productive age program implementer, and the person in charge of the productive age program. The data analysis used in this research is case study analysis with data processing using a qualitative data processing application, namely Nvivo version 14. Management of BOK funds at the Sei Agul Community Health Center, Medan City has obstacles, namely adjusting the Community Health Center program with the Health Service program. In its implementation there are obstacles, namely the slow realization of the BOK budget and a less active community. Reporting has obstacles, namely too many reporting files and too short a time. In the evaluation, there were solutions to obstacles to program implementation that were not followed up.